A Study of Circulation, Turbulence, and Tidal Stream Resources in the Taiwan Strait - Korotenko, Konstantin A.; Zavialov, Peter O.; Chen, Yang-Yih; Lee, Hsien Hua (Frontiers in Marine Science, 2020)
The 3-D Princeton Ocean Model with tidal forcing supplied by 2-D barotropic model) was used to examine the time-depth variability and features of tidal current, turbulence and power density with a special reference to assess potential tidal stream energy resources in the Taiwan Strait (TS). Numerical simulations showed that semidiurnal tidal currents are predominant in the TS, with along-channel mean amplitudes exceeding 1.0 ms−1. Over the Chang-Yuen Rise (CYR) and in the Peng-Hu Cannel (PHC) turbulence exhibits symmetry while in the cross-slope direction to the south from the CYR turbulent asymmetry changes from ebb-dominant to flood-dominant. The maximum values of eddy diffusivity within the bottom boundary layer of about 10 m ranged from ~10-3 to 10-2 m2 s-1. The simulation revealed that, in the PHC, bottom shear turbulence, on the ebb, is suppressed by strong stratification due to the inflowing of dense water from the South China Sea. Numerical simulations revealed several potentially attractive locations for tidal turbines in the TS where power density had relative low flood/ebb asymmetry and exceeded 100 Wm-2. In the PHC, a highly attractive site where power density exceeded 300 Wm-2 was identified near the PH Archipelago.